Anaerobic Fluidized Bed Reactor (AFBR) for the treatment of high solid content agro-industrial wastewater - Mamun, Abdullah Al; Idris, Azni (Global Science Publications, 2021)
Palm oil mill effluent (POME) is a high strength agro-industrial wastewater that contains significant amount of organic suspended solids. These solids reduce plant efficiency and account for additional maintenance of fixed bed digesters. An anaerobic fluidized bed reactor was studied to evaluate the performance of the system to treat solids from the POME. The hydraulic retention time (HRT) was reduced step wise from 24 hr to 4 hr, which resulted in volumetric loading rates of 4.0 kg COD/m3.d to 13.8 kg COD/m3.d, respectively. The maximum TSS removal rates varied in the range of 68% - 89%. The AFBR showed promising performance without exhibiting any problem pertaining to the solids in the wastewater. The AFBR exhibited low sludge production with sludge volume indices (SVI) of between 11 L/mg and 35 L/mg. The low SVI indicates fast settleability and self-compressibility of the digested solid particles in POME. The study showed the superiority of AFBR over the other treatment processes in treating industrial wastewater that contains significant portion of solids.